ANALYSIS OF FACTORS THAT INFLUENCE CUSTOMER LOYALTY IN WAPRES COFFEE - Febrian Reinaldy Siahaan; Junfrian Hangoluan Lumban gaol; Eka Mayastika Sinaga; Imelda Mardayanti (CV. Radja Publika, 2026)
This study aims to analyze the factors that influence customer loyalty at Wapres Coffee, focusing on Generation Z customers. The factors studied include product quality, service quality, price, and cafe atmosphere. This study uses a quantitative approach with a survey method. The research sample consisted of 100 respondents selected using a purposive sampling technique, with the criteria of having made at least two purchases and being among Generation Z. Data collection was carried out through a structured questionnaire with a 5-point Likert scale. Data analysis used Structural Equation Modeling based on Partial Least Square (PLS) with the help of SmartPLS 3.0. The results showed that product quality (t = 2.429; p = 0.015) and cafe atmosphere (t = 2.108; p = 0.036) had a positive and significant effect on customer loyalty. Conversely, service quality (t = 0.996; p = 0.320) and price (t = 1.226; p = 0.221) were not proven to have a significant effect on customer loyalty. Product quality is the most dominant factor in shaping customer loyalty, with a path coefficient of 0.351. An R-squared value of 0.727 indicates that the four independent variables can explain 72.7% of the variation in customer loyalty. This study confirms that consistent product quality and a comfortable cafe atmosphere are key to building and maintaining Generation Z customer loyalty at Wapres Coffee.